2020
DOI: 10.1007/s00521-020-04737-6
|View full text |Cite
|
Sign up to set email alerts
|

Tracking changes in user activity from unlabelled smart home sensor data using unsupervised learning methods

Abstract: This paper investigates the utility of unsupervised machine learning and data visualisation for tracking changes in user activity over time. This is done through analysing unlabelled data generated from passive and ambient smart home sensors, such as motion sensors, which are considered less intrusive than video cameras or wearables. The challenge in using unlabelled passive and ambient sensors data for activity recognition is to find practical methods that can provide meaningful information to support timely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Many data analysis problems, reaching from population analysis to computer vision [6,28], require estimating continuous models from discrete samples. Formally, this is the density estimation problem, where, given a sample fx i g $ pðxÞ, we would like to estimate the probability density function (PDF) p(x).…”
Section: Introductionmentioning
confidence: 99%
“…Many data analysis problems, reaching from population analysis to computer vision [6,28], require estimating continuous models from discrete samples. Formally, this is the density estimation problem, where, given a sample fx i g $ pðxÞ, we would like to estimate the probability density function (PDF) p(x).…”
Section: Introductionmentioning
confidence: 99%
“…An additional important class of approaches, which has been applied in limited cases for AAL systems, are those that are based on unsupervised learning techniques. They can be applied for the clustering of large amounts of unlabelled data, grouping user behaviors, and detecting high-level variations without any prior knowledge or training phase [117,118]. This study has identified several clusters of options for data processing in AAL, depending on the complexity of the target.…”
Section: Methodologies For Data Analysismentioning
confidence: 99%
“…However, removing human agency from the training phase also removes any possibility for ethical accountability and oversight from the critical part of machine learning. In response we see a series of human-in-the-loop solutions that have tried to combine the engineering benefits of these approaches with the accountability of human agency (Gupta et al 2020, Sloane et al 2020). These include fairness analytics tools such as AIFairness360, the What-If tool, and explainability tools such as LIME.…”
Section: Machine Learning and Its Ethical Discontentmentioning
confidence: 99%